2013
DOI: 10.3201/eid1911.121470
|View full text |Cite
|
Sign up to set email alerts
|

CTX-M β-Lactamase–producingKlebsiella pneumoniaein Suburban New York City, New York, USA

Abstract: CTX-M extended-spectrum β-lactamase (ESBL)–producing Klebsiella pneumoniae isolates are infrequently reported in the United States. In this study, we analyzed nonduplicate ESBL-producing K. pneumoniae and Escherichia coli clinical isolates collected during 2005–2012 at a tertiary care medical center in suburban New York City, USA, for the presence of blaCTX-M, blaSHV, blaTEM, and blaKPC genes. Despite a high prevalence of blaCTX-M genes in ESBL-producing E. coli since 2005, blaCTX-M genes were not detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
1
36
3
1
Order By: Relevance
“…K. pneumoniae ST147 isolates that are resistant to diverse antibiotics have disseminated worldwide (15)(16)(17)(18)(19); however, ST147 isolates, to our knowledge, have not been found in K. pneumoniae from South Korea. Therefore, we suggest that pCC1409-1 and pCC1410-1 were not derived from K. pneumoniae isolates found in South Korea.…”
mentioning
confidence: 90%
“…K. pneumoniae ST147 isolates that are resistant to diverse antibiotics have disseminated worldwide (15)(16)(17)(18)(19); however, ST147 isolates, to our knowledge, have not been found in K. pneumoniae from South Korea. Therefore, we suggest that pCC1409-1 and pCC1410-1 were not derived from K. pneumoniae isolates found in South Korea.…”
mentioning
confidence: 90%
“…The high rate of ESBL producers among clinical isolates in the developing world is troublesome due to lack of financial support for effective infection control and limited sources of effective antimicrobials. These factors have a clear impact on the morbidity and mortality related to infections caused by ESBL producers This study demonstrated that bla SHV was the most common resistance determinant accounting for 51.9% of the K. pneumoniae isolates, followed by bla CMY, blaDHA, bla TEM and bla CTX-M at rates of 16.7%, 13 %, 9.2% and 7.4% , respectively, These findings are lower than the results reported by Guiqing Wang and co-workers in USA (22) who detected bla SHV and bla TEM genes at rates of 84.3% and 50.4%, respectively In contrast, the study of Parveen et al( 2011) in India, reported bla CTX-M as the most common ESBL-type among K. pneumonia isolates from blood, and 92% of their strains were ESBLs-producers, including high rates prevalence of bla TEM (82%) and bla SHV 46% (23).…”
Section: Discussioncontrasting
confidence: 56%
“…3 β-lactamases including broad-and extended-spectrum β-lactamases (ESBLs) have been reported predominantly in Enterobacteriaceae, especially Klebsiella pneumoniae (K. pneumoniae) and Escherichia coli (E. coli). [4][5][6] Most extended-spectrum β-lactamases fall into three genotypes: TEM, SHV and CTX-M 7 with hundreds of variants of these gene families having emerged and disseminated widely requiring concerted efforts to effectively control. 6,8 An example is the 4130 allelic variants of CTX-M (Lahey Clinic website: http://www.lahey.org/Studies/other.asp#table1).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Most extended-spectrum β-lactamases fall into three genotypes: TEM, SHV and CTX-M 7 with hundreds of variants of these gene families having emerged and disseminated widely requiring concerted efforts to effectively control. 6,8 An example is the 4130 allelic variants of CTX-M (Lahey Clinic website: http://www.lahey.org/Studies/other.asp#table1). 9 Other β-lactamases including AmpC, carbapenemases and OXA-type enzymes have also been consistently reported to cause antibiotic resistance in Enterobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%